FREQUENCY OF INTRA CRANIAL COMPLICATIONS IN CHRONIC OTITIS MEDIA - Hussain, Ajmal; Khan, Arif Raza (Journal of Ayub Medical College Abbottabad, 2005)
Background: Chronic Otitis Media can lead to intracranial complications, which were more common in pre-antibiotic era as compared to the present antibiotic era. Patients of Chronic Otitis Media with intracranial complications usually present very late due to ignorance and lack of primary health care. The aim of this study was to investigate, the frequency, mortality and morbidity of intracranial complications of chronic otitis media admitted in Ear Nose and Throat Unit of Lady Reading Hospital Peshawar. Methods: This study was conducted in Government Lady Reading Hospital Peshawar for a period of two years from October 2001 to October 2003. All the patients diagnosed as intracranial complications of chronic otitis media were included in the study. Result: The total number of patients reporting with intracranial complication due to chronic Otitis media (Unsafe ear) was 20. Meningitis and brain abscess were present in 8 cases each (40%). In 3 cases (15%) extradural abscess was found while 1 (5%) had lateral sinus thrombosis. Conclusion: Chronic Otitis media is a common disease in our part of the world. Key word: Chronic Otitis Media, Intracranial complications, Brain abscess, Meningitis.